Interactive Elastic Buckling of Thin-Walled Closed Orthotropic Beam-Columns - Kołakowski, Z.; Królak, M. (Engineering Transactions, 1995)
The present paper deals with an analysis of global and local stabilities and with the investigation of equilibrium paths in the initial post-buckling behaviour of elastic thin-walled beam-columns consisting of orthotropic rectangular walls. Closed or open cross-section beam-columns, simply supported at the ends, are subject to axial compression, eccentric compression or pure ben ding. The problem is solved by means of a variational method using the asymptotic nonlinear theory of stability of the conservative systems [7, 8]. Numerical calculations employ Byskov’s and Hutchinson’s asymptotic expansion [3] in the form of the transition matrix method. The calculation is restricted to the first order nonlinear approximation. The analysis is carried out in order to study the influence of the wall orthotropy factor of dosed cross-section beam-columns (square or trapezoid-shaped) subject to axial and eccentric compression influences the critical state and the initial post-buckling behaviour.